Sistem Pendukung Keputusan dengan Metode SAW, WP, dan TOPSIS Untuk Pemilihan Lokasi Wisata Terbaik - Aditya Putra Maulana; Diah Prastyani; Muhammad Bryan Putra; Muhammad Rafli Efendi; Prameswari Balqis; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The tourism industry plays a vital role in driving economic growth in a region. However, the abundance of tourist destination choices often makes it difficult for travelers to select the most suitable location based on their preferences and needs. To address this issue, a Decision Support System (DSS) is needed to provide recommendations in an objective and structured manner. This study aims to design a DSS using multi-criteria decision-making methods, namely Simple Additive Weighting (SAW), Weighted Product (WP), and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS), to determine the best tourist destinations based on several criteria such as accessibility, facilities, cost, and popularity. These methods have been proven effective in enhancing the accuracy and efficiency of decision-making. By leveraging information technology and appropriate algorithms, the system is expected to assist tourists, destination managers, and local governments in selecting and developing optimal tourist destinations.